2017
DOI: 10.1038/s41598-017-10111-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization patterns and minimum screening panels for aeroallergens in self-reported allergic rhinitis in China

Abstract: Optimization of skin prick test (SPT) panels, especially in view of significant differences in sensitizations patterns within different geographical areas, is an unmet need within China. Our aim was to assess the patterns and clinical relevance of aeroallergen sensitizations in allergic rhinitis (AR) and define the minimal battery of SPT allergens, classified according to the Köppen-Geiger climate map. Overall, 7148 subjects with self-reported AR completed a standard questionnaire and were assessed for sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 27 publications
(57 reference statements)
3
63
1
Order By: Relevance
“…Combined with medical history, nasal symptoms, and the endoscopic examination, 39 patients were diagnosed to have allergic rhinitis. These findings are in accordance with the findings of Lou et al, who demonstrated that mugwort and Der f were the most prevalent sensitizing aeroallergens for AR throughout China. In accordance with the findings of other studies, the present study also demonstrated that 25% of the allergic rhinitis patients had comorbid asthma.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Combined with medical history, nasal symptoms, and the endoscopic examination, 39 patients were diagnosed to have allergic rhinitis. These findings are in accordance with the findings of Lou et al, who demonstrated that mugwort and Der f were the most prevalent sensitizing aeroallergens for AR throughout China. In accordance with the findings of other studies, the present study also demonstrated that 25% of the allergic rhinitis patients had comorbid asthma.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the prevalence of mugwort was significantly higher than the prevalence of Der f , most likely because the study was conducted in August, the autumn season in Beijing during which the most prevalent aeroallergen in northern China is mugwort . Although the house dust mite allergen demonstrated high prevalence in the present study, this aeroallergen has the highest sensitization in southern China.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In the population of northern China, patients who experience pollinosis are most frequently allergic to grass pollens, particularly Artemisia . Because of the large number of grass species, the duration of the grass pollen season is approximately 3 months in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…The species and concentrations of airborne pollen vary according to geographical location, weather conditions, and season. A recent multicenter epidemiologic study in China revealed that grass pollens were the most prevalent sensitizing aeroallergens in north China; in particular, sensitization rates for Artemisia pollen were 58.2% in northwest China . Another epidemiological study in the northern grassland regions of China also suggested that grass pollens were the most common allergens .…”
mentioning
confidence: 99%